Out-of-plane response of masonry walls strengthened using textile-mortar system. (20th March 2018) - Kariou, F.A.; Triantafyllou, S.P.; Bournas, D.A.; Koutas, L.N.
Highlights: The out-of-plane response of TRM strengthened walls is investigated. TRM effectiveness significantly depends on the wall thickness. Textile reinforcement coating significantly enhances the effectiveness of TRM. An in-house coating procedure is proposed for this purpose. Abstract: The out-of-plane response of masonry walls strengthened with textile-reinforced mortar (TRM) is experimentally investigated in this work. Medium-scale three-point bending tests were carried out on 18 specimens comprising a set of 9 single-wythe and 9 double-wythe brick masonry walls. Key investigated parameters involved the textile reinforcement ratio, the textile material, the coating of the textile reinforcement with epoxy resin, and the wall thickness. Experimental results suggest that TRM significantly increase the load bearing capacity of masonry walls. The amount of reinforcement utilised affects both the strength and deformation characteristics of the corresponding specimens, while it may alter the failure mode. Resin coating on the textile is found to be beneficial for the performance of the TRM overlays.